A modified approach for vestibuloplasty in severely resorbed mandible using an implant-retained postoperative stent: a case report - Melo, Luiz Gustavo N. [UNESP]; Almeida, Ana Lucia P. F.; Scarelli Lopes, Jose Fernando; Rezende, Maria Lucia R.; Neto, Jose Sergio M.; Ciporkin, Frederico; Nagata, Maria José Hitomi [UNESP] (Mosby-elsevier, 2008)
Background. Severely resorbed mandibles often present a short band of keratinized tissue associated with a shallow vestibule. As a result, prominent muscle insertions are present, especially in the mental region of the mandible. This case report describes the deepening of the vestibular sulcus in an atrophic mandible by combining free gingival grafts harvested from the palate and a postoperative acrylic resin stent screwed on osseointegrated implants placed at the anterior region of the mandible.Study design. During the second-stage surgery, a split-thickness labial flap was reflected and apically sutured onto the periosteum. Two free gingival grafts were obtained and then sutured at this recipient site. A previously custom-made acrylic stent was then screwed onto the most distally positioned implants. To document the procedure's stability over time, a metal ball was placed in the most apical part of the vestibule and standardized cephalometric radiographs were taken before and 6 months after the procedure. Linear measurements of vestibular depths over the observation time were realized using specific software for radiographic analysis.Results. The proposed technique augmented the band of attached masticatory mucosa, deepened the vestibule and prevented the muscle reinsertion. The difference between the 2 measurements of vestibular depths was 9.39 mm (initial 20.88 mm, final 11.49 mm) after a 6-month postoperative period.Conclusion. The technique, in combination with palatal mucosal graft and use of a postoperative stent, decreased the pull of mentalis muscle and provided a peri-implantally stable soft tissue around implants. (Oral Surg Oral Med Oral Pathol Oral Radiol Endod 2008; 106: e7-e14)